On Social Revolutions and Restorations in Modern History - Norkus, Zenonas (Problemos, 2022)
Sharp opposition between revolution as a positively valued and dominant term and restoration as its subordinated complement, loaded with negative meaning, is one of the legacies of the 1789 French Revolution. This may be the main reason why social restorations still are neglected in the philosophy of history and historical sociology, although both types of modern revolutions (French 1789 or “bourgeois” and Russian 1917 or “socialist”) did end with restorations. This paper proposes revisions to only attempt at the theory of social restorations (by Austrian American comparativist Robert Kann (1906-1981) to make it applicable to post-communist restorations. They include the distinction between type and token restorations, endurance and performance success of restorations, and a new formulation of the criterion of endurance success.